Wet peroxide oxidation of phenol over carbon/zeolite catalysts. Kinetics and diffusion study in batch and flow reactors; Journal of Environmental Chemical Engineering; Vol. 6, iss. 2 - Taran O. P. Oxana; Zagoruiko A. N. Andrey Nikolaevich; Yashnik S. A. Svetlana; Ayusheev A. B. Artemiy; Pestunov A. B. Andrey; Prosvirin I. P. Igor; Prihod’ko R. V. Roman; Goncharuk V. V. Vladislav; Parmon V. N. Valentin (2018, 2018)
Title screen